Repeated impact of simulated hail ice on glass fibre composite materials - Macdonald, Hamish; Nash, David; Stack, Margaret M. (Wear, 2019)
Wind turbine blade damage, particularly leading edge erosion, is a significant problem faced by the renewable energy industry. Wind turbines are subject to a wide range of environmental factors during a 20 + year lifespan, with hailstones often touted as a key contributor to the deterioration of the blade profile. An experimental campaign was carried out to investigate the effects of repeated impact of smaller diameter simulated hail ice (SHI) on composite materials, to correspond to those most prevalent at wind farm locations. Hailstones of four different diameters (5 mm, 10 mm, 15 mm and 20 mm) were fired at velocities in the range of 50 ms−1 to 95 ms−1. Samples used for experimentation were manufactured from triaxial stitched glass fibre [0°/−45°/+45°] and epoxy resin. Damage was evaluated in terms of sample mass loss and microscopy of the composite surface. For all examples, mass loss was negligible and optical microscopy showed little evidence of surface damage. Surface degradation was discernible under scanning electron microscopy for the larger diameter SHI (≥15mm), with projectile velocity a notable factor in the extent of the damage. Even for large numbers of impacts, there was little noteworthy damage caused by smaller, more prevalent SHI (≤10mm). This suggests that hail is not a direct cause of wind turbine blade erosion. •Repeated impact of more prevalently sized hailstones did not result in notable erosive mass loss of wind turbine blade materials.•Little noteworthy damage was observed using optical microscopy but damage was found under scanning electron microscopy.•Damage was encountered for the larger hailstones at higher velocities, indicating a damage threshold velocity.•Little noteworthy damage was found for the smaller, more prevalent diameter hailstones, indicating that hail is not a direct cause of wind turbine blade erosion.